1989
DOI: 10.3171/jns.1989.71.3.0403
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nimodipine and dextran on axonal function and blood flow following experimental spinal cord injury

Abstract: There is evidence that posttraumatic ischemia is important in the pathogenesis of acute spinal cord injury (SCI). In the present study spinal cord blood flow (SCBF), measured by the hydrogen clearance technique, and motor and somatosensory evoked potentials (MEP and SSEP) were recorded to evaluate whether the administration of nimodipine and dextran 40, alone or in combination, could increase posttraumatic SCBF and improve axonal function in the cord after acute SCI. Thirty rats received a 53-gm clip compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(76 citation statements)
references
References 43 publications
(3 reference statements)
0
74
0
2
Order By: Relevance
“…After experimental TSCI, a profound reduction in spinal cord blood flow occurs, which progressively worsens (21) and may last for 24 h (22). In a recent study assessing the effects of EPO on the clinical course after subarachnoid hemorrhage in a rabbit model, rhEPO treatment dramatically attenuated the intense intracerebral arterial spasm Extensive white matter preservation can be observed in the rhEPO-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…After experimental TSCI, a profound reduction in spinal cord blood flow occurs, which progressively worsens (21) and may last for 24 h (22). In a recent study assessing the effects of EPO on the clinical course after subarachnoid hemorrhage in a rabbit model, rhEPO treatment dramatically attenuated the intense intracerebral arterial spasm Extensive white matter preservation can be observed in the rhEPO-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Changes in evoked potential amplitude correlate with severity of the SCI and posttraumatic ischemia, and the latter is reversible by pharmacological intervention. Increase in SCBF at the site of SCI correlates with improvement in the function of acutely injured spinal axons, 25,29 and glutamate signaling may play a role in modulation of blood¯ow and blood brain barrier permeability. 30 Therefore, we hypothesize that treatment with an NMDA antagonist after acute SCI would a ect axonal function by blocking NMDA receptors and reducing neurotoxicity at the injury site, and that there would be an increase in blood¯ow and a decrease in edema in the injured spinal cord.…”
Section: Introductionmentioning
confidence: 95%
“…A majority of studies reported significant posttraumatic hypoperfusion in adjacent segments of spinal cord. [17][18][19] Likewise, a number of clinical and experimental studies had shown less cerebral blood flow in and around contused brain parenchyma. 20,21 However, this study showed that on CDFI and CEUS there was a correspondingly significant hypervascularity and hyperperfusion in the adjacent region, which at least lasted 120 min.…”
Section: Discussionmentioning
confidence: 99%